Assessing climate impacts on slow-moving landslides in the western Alps of Piemonte: integration of monitoring techniques for detecting displacements - Narcisi, Roberta; Pappalardo, Salvatore Eugenio; Taddia, Glenda; De Marchi, Massimo (Frontiers in Earth Science, 2024)
The influence of climatic factors on landslides triggers and displacement rates is one of the most widespread research topics, especially due to the growing need to understand the evolution of climate change in historical periods of intense precipitation and anomalous temperature increases. Italy, highly prone to hydrogeological instability, extremely its mountainous regions such as the Alps, stands as a pertinent subject area for instability scenarios. However, the interpretation of climate effects on landslides is still an open issue. This work proposed a simplified methodology for investigating the displacements of three slow-moving landslides located in the western Alps of Piemonte region, in response to significant meteorological events evaluated from precipitation and temperature trends over the reference period 1991-2020. Another purpose is to emphasize the advantages of using different monitoring techniques, both in situ and remote sensing, to detect ground deformation processes of these gravitational phenomena. The existence of a robust monitoring network, coupled with InSAR dataset support, has allowed detecting climatic factors' impact on displacement rates for the outlined case studies. The results have demonstrated the relationships between the identified climatic events and variations in displacement time series, as well as the potential of integrating field observations and InSAR techniques to improve the interpretation of landslide dynamics.